2021
DOI: 10.1186/s12874-021-01392-w
|View full text |Cite
|
Sign up to set email alerts
|

Can the adverse childhood experiences (ACEs) checklist be utilized to predict emergency department visits among children and adolescents?

Abstract: Background Extensive literature has shown an association of Adverse Childhood Experiences (ACEs) with adverse health outcomes; however, its ability to predict events or stratify risks is less known. Individuals with mental illness and ACE exposure have been shown to visit emergency departments (ED) more often than those in the general population. This study thus examined the ability of the ACEs checklist to predict ED visits within the subsequent year among children and adolescents presenting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Characterization of this association provides supportive evidence for incorporating risk factors such as early adversity into a more individualized risk profile, which may help with clinical triage and mapping to the appropriate supports and level of care for students seeking mental health support. 1 , 61 Psychosocial factors (i.e., perceived stress, low self-esteem, and low sleep quality) identified as mediators in the study should be further explored through intervention studies as targets to mitigate the harms to mental health associated with childhood adversities. Student-tailored mental health literacy may support the development of healthy socioemotional coping resources and facilitate timely help-seeking through reduced stigma 62 and increased emotional self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of this association provides supportive evidence for incorporating risk factors such as early adversity into a more individualized risk profile, which may help with clinical triage and mapping to the appropriate supports and level of care for students seeking mental health support. 1 , 61 Psychosocial factors (i.e., perceived stress, low self-esteem, and low sleep quality) identified as mediators in the study should be further explored through intervention studies as targets to mitigate the harms to mental health associated with childhood adversities. Student-tailored mental health literacy may support the development of healthy socioemotional coping resources and facilitate timely help-seeking through reduced stigma 62 and increased emotional self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this exploratory study aims to build a better picture of CYP who experience suicidal crises, by examining the ACEs and socio-demographic characteristics associated with ED presentations at a local children's hospital over a two-year period. Furthermore, given the association between the length of the suicidal crisis and future suicide attempts [8], the study aims to examine the factors associated with repeated attendance at ED for suicidal crisis; in other words, the ACEs and other socio-demographic characteristics associated with pervasive and enduring crises. Thus, the research questions for the current study are as follows:…”
Section: Aces and Use Of Healthcare Servicesmentioning
confidence: 99%
“…Indeed, research suggests that suicidal ideation often precedes a suicide attempt; for example, a longitudinal study in the US found that more than one-third of adolescents in suicidal crisis went on to attempt suicide [7]. Furthermore, it has been shown that the more pervasive the suicidal crisis, the more likely the individual is to attempt suicide [8]. In the UK, 42% of young adults reported having suicidal thoughts on at least one occasion in the previous twelve months [9].…”
Section: Introductionmentioning
confidence: 99%
“…ACEs can induce mental (Barnhart et al, 2022; Weller et al, 2021) and physical health issues (Kovács‐Tóth et al, 2021), as well as substance abuse (Bomysoad & Francis, 2020) and poor academic success (Myat Zaw et al, 2022) during the adolescence period. Consequently, ACEs lead to higher healthcare visits among adolescents (Bhattarai et al, 2021; Lackova Rebicova et al, 2022). The evidence reveals that although ACEs may negatively influence adolescents' well‐being (Kelifa et al, 2021), this warrants examination in various cultural contexts because subjective well‐being regards individuals' interests and positive effects (Diener, Heintzelman, et al, 2017) as distinctively shaped by culture (Tov & Diener, 2009).…”
Section: Introductionmentioning
confidence: 99%